2015
DOI: 10.2105/ajph.2014.302479
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behavior, Sexual Violence, and HIV in Persons With Severe Mental Illness in Uganda: Hospital-Based Cross-Sectional Study and National Comparison Data

Abstract: Findings suggest that SMI exacerbates Ugandan women's sexual vulnerability. Public health practitioners, policymakers, and legislators should act to protect health and rights of women with SMI in resource-poor settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…Table 3 displays measurement of violence within the 174 included manuscripts and reports. Of the included manuscripts and reports, n = 134 measured multiple types of violence, whereas n = 18 focused only on sexual violence [ 41 , 45 , 53 , 56 , 58 , 59 , 66 , 85 , 86 , 88 , 93 , 100 , 108 , 109 , 118 , 122 124 ], n = 13 focused only physical violence [ 76 , 77 , 84 , 103 , 112 , 116 , 125 – 132 ] and one study focused only on economic abuse [ 133 ]. Physical violence was assessed in n = 146 manuscripts or reports, sexual violence was assessed in n = 144, psychological violence (including items defined by authors as emotional abuse or controlling behaviors, verbal abuse and threats) was assessed n = 87 and economic violence was assessed in n = 17 manuscripts or reports.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 displays measurement of violence within the 174 included manuscripts and reports. Of the included manuscripts and reports, n = 134 measured multiple types of violence, whereas n = 18 focused only on sexual violence [ 41 , 45 , 53 , 56 , 58 , 59 , 66 , 85 , 86 , 88 , 93 , 100 , 108 , 109 , 118 , 122 124 ], n = 13 focused only physical violence [ 76 , 77 , 84 , 103 , 112 , 116 , 125 – 132 ] and one study focused only on economic abuse [ 133 ]. Physical violence was assessed in n = 146 manuscripts or reports, sexual violence was assessed in n = 144, psychological violence (including items defined by authors as emotional abuse or controlling behaviors, verbal abuse and threats) was assessed n = 87 and economic violence was assessed in n = 17 manuscripts or reports.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, evidence of dangerous sexual behaviors between men and women has been cited in the literature. Lundberg et al [24] found a high presence of multiple sexual partners among men with a mental illness compared to women, and a higher association between high-risk sexual behaviors and being HIV-infected among men. Contradictory findings from previous studies, however, attributed a higher risk of HIV infection from high risk behavior to women [7,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of syphilis comorbidity in this Ugandan study was twice that reported in a Brazilian study (1.1%) a country where the general prevalence of syphilis is reported at 7.7% among women attending antenatal care (38). Both vulnerability to HIV and syphilis which are predominantly transmitted through heterosexual relationships in the SMI context in Uganda are underlined by a common vulnerability to risky sexual behaviour and sex violence which Lundberg and colleagues (2015) in their Ugandan study reported to be more prevalent in SMI than in the general population (39).…”
Section: Discussionmentioning
confidence: 99%